Measurement of Entrepreneurial Orientation, Network Capability, Inter-Firm Partnerships, Marketpreneur, and Business Performance among MSME Entrepreneurs Demographics - Lestari, Asih Arum; Rika Fatimah, P.L. (Jurnal Manajemen Teknologi, 2025)
Abstract. The entrepreneurial characteristics of opportunity-seeking, proactiveness, collaboration, and customer and market foresight are essential drivers of success for Micro, Small, and Medium Enterprises (MSMEs). Previous studies have widely examined entrepreneurial orientation (EO), network capability (NC), inter-firm partnerships (IFP), and business performance (BP), yet their interactions and implications within the demographic context of MSME entrepreneurs remain underexplored. The drive of MSME actors to innovate, collaborate, and expand into broader markets serves as a vital foundation for enhancing competitiveness and business performance. However, Indonesia’s rapidly evolving MSME landscape requires fresh insights that reflect the distinctive and actual on-the-ground realities faced by these enterprises. This study aims to measure the dimensions of entrepreneurial orientation, network capability, inter-firm partnership, and marketpreneur characteristics and how these relate descriptively to MSME business performance across different demographic categories in Indonesia. This research adopts a descriptive quantitative approach involving 153 MSME respondents in Indonesia, and the research analysis is conducted through cross-tabulation analysis and categorization using the Total Cell Ratio (TCR). The findings reveal variations in entrepreneurial orientation, networking skills, partnership engagement, and marketpreneur behavior across gender, education, and job position groups. The study contributes to the literature by presenting an integrated measurement of MSME entrepreneurial competencies while contextualizing demographic associated with. Furthermore, it provides insights for policymakers and MSME practitioners to strengthen entrepreneurial capacity through networking and market-driven innovation. Keywords: Network capability, inter-firm partnerships, business performance, entrepreneurship orientation, marketpreneur (tetrapreneur model), MSME actor demographics